Practice and thinking of online teaching for nursing students during the COVID-19 epidemic prevention and control (新型冠状病毒肺炎疫情防控期间护理实习生线上教学的实践与思考) - SONG Yawen (宋雅文); ZHOU Lin (周林); WU Mengment (武蒙蒙); WAN Bingrou (万冰柔); WU Qingyun (吴青云) (中西医结合护理)
The online teaching method was adopted to ensure the orderly implementation of teaching plan and schedule during the COVID-19 epidemic prevention and control. Based on the preparation of online etching, multiple methods and characteristic online teaching management were carried out to ensure successful teaching plan completion. (线上教学有效保障了新型冠状病毒肺炎疫情防控期间护理实习生教学进度的推进, 在充分做好线上临床教学准备工作的前提下, 采用多种方式开展教学活动, 进行特色线上教学管理, 有助于临床教学计划的顺利完成。)